Biosynthesis of Silver Nanoparticles by Bamboo Leaves Extract and Their Antimicrobial Activity (Journal of Fiber Bioengineering and Informatics, 2013)
The synthesis of nanoparticles from biological processes is evolving a new era of research interestsin nanotechnology. Silver nanoparticles are usually synthesized by chemicals which are quite toxicand flammable in nature. This study deals with an environment friendly and biosynthesis process ofantibacterial silver nanoparticles using bamboo leaves. The formation and characterisation of AgNPswere confirmed by UV-Vis spectroscopy, energy-dispersive spectroscopy (EDX), X-ray diffraction (XRD)and transmission electron microscope (TEM). The antimicrobial activities were carried out against E.coli and S. aureus strains by using disc diffusion method.
Keywords: Silver Nanoparticles; bamboo Leaves; Green Synthesis; Antibacterial